X-Ray Repair Cross Complementing 4 (XRCC4) Gene Expressions as Biomarkers for Detection of Ionizing Radiation Exposure - Ali, Abdulsahib K. (University of Thi-Qar Journal of Science, 2019)
The present study aims at using the gene expression as biomarkers in the identification of the biological effects of low and high doses of ionizing radiation (X-ray) in white mice Mus musculus Balb/C, ages 4-6 weeks, weight 30-40 grams. Seventy- two white mice (36 males and 36 females) were divided into two groups; their whole body was exposed to 5 cGy (rad) and 100 cGy (rad) of X-ray radiation at a dose rate of 200 cGy/min, in addition to the control group. Total RNA was successfully isolated using Trizol method from blood and liver samples of mice after 6, 48 hours and 10 days of exposure to radiation as well as of the control group. The RNA concentration was determined spectrophotometrically by measuring their absorbance using nucleic acid and protein analyzer that dependent on the ratio A260/A280 of the wavelength which lead to the determination of RNA purity, it ranged from 1.79-2.1 in all mice groups. RNA integrity and quality were confirmed by agarose gel electrophoresis.Three bands such as 28s, 18s and 5s appeared in a visible manner. This study involved the reverse transcription (RT) of the RNA for the manufacture of complementary DNA (cDNA) using the polymerase chain reaction (PCR) for investigation on above –mentioned groups of animals. Complementary DNA was used in amplification of genes used in the present study, one type of specialized primers were selected for the gene as X-Ray repair cross complementing group 4 (XRCC4), which have a relation with ionizing radiation in addition to the primers for internal control (β-actin) gene. The optimal conditions for PCR were determined using a dye (SYBR®Green 1).This should be done before using the device quantitative real time-PCR (QRT-PCR) in experiments. The products of replicated specialized primers for the genes concerned and the cDNA for the studied samples were electrophoretically separated in agarose gels .The banding profiles were visualized by ethidium bromide staining, as the molecular weight was 183 bp nitrogen-base pair for XRCC4 gene.The changes in the gene expression for the genes concerned were determined by measuring the quantitative levels of expression in the blood and liver samples of the group of mice after 6, 48 hours and 10 days of exposure to X-ray, in addition to the control group using the device QRT-PCR.The presence of significant reduction (p <0.05) in the amount of gene expression for the XRCC4 gene in samples of blood and liver from mice exposed to both doses of 5 cGy and 100 cGy after 6, 48 hours and 10 days of exposure to radiation. This gene was down-regulation after 6 hours in the blood samples of mice exposed to these doses compared to the control group. In contrast, there were to these finding, significant increases (p <0.05) in the amounts of gene expression of this gene in the liver tissues of mice exposed to both doses after 6 and 48 hours of exposure to radiation. This gene also showed up-regulation after 48 hours in the liver tissue of mice exposed to 5 cGy doses, while the up-regulation was appeared after 6 hours of exposure to 100 cGy dose of radiation.In conclusion, the results indicated that there is a possibility of using the changes in the level of XRCC4 gene expression as useful biomarkers for the detection of organism’s exposure to ionizing radiation.